Integrasi Ilmu Pengetahuan Dan Nilai Islam Menggunakan Pendekatan Studi Islam Interdisipliner: Surah Al-‘Ashr Ayat 1-3 - Anton Wijaya Kusuma Kusuma (Al-Fath, 2024)
ABSTRACT The Interdisciplinary Islamic Studies approach plays a central role in responding to the complex dynamics and diversity of Islamic understanding in the midst of the globalization era. This article explores the role of the integration of science and Islamic values as the main foundation of this approach. By analyzing the contribution of this integration in the context of Islamic studies, this research aims to reveal how this approach is able to form a holistic understanding that not only includes academic dimensions, but also Islamic spiritual values. The research methods applied are analytical and qualitative, allowing for an in-depth investigation into the role of the integration of science and Islamic values. The analytical approach is used to understand the impact of the interdisciplinary approach, while the qualitative approach allows for an in-depth exploration of the experiences and views of experts and practitioners involved in interdisciplinary Islamic studies.